Nomenclatorial note on Bernaeinae (Hemiptera, Sternorrhyncha, Aleyrodidae) - Shcherbakov, Dmitry E.; Drohojowska, Jowita; Szwedo, Jacek (Zootaxa, 2020)
The Bernaeinae, currently regarded as a subfamily of Aleyrodidae (Szwedo & Drohojowska 2016, Drohojowska et al. 2019), is the only extinct subfamily of whiteflies with a fossil record from the Callovian (late Middle Jurassic) to Cenomanian (early Upper Cretaceous). Currently, it comprises seven species in six genera (Schlee 1970, Shcherbakov 2000, Drohojowska et al. 2019, Chen et al. 2020)—Bernaea neocomica Schlee, 1970; Burmoselis evelynae Shcherbakov, 2000; Heidea cretacica Schlee, 1970 (see comment below); Juleyrodes Shcherbakov, 2000 (J. gilli Shcherbakov, 2000, J. visnyai Shcherbakov, 2000), Paraburmoselis kachinensis Chen, Zhang, Wang et Zheng, 2020 and Sinicoselis weberi Drohojowska, Wegierek, Evans et Huang, 2019. Heidea by mistake was figured in Drohojowska & Szwedo (2011a, p. 192, Fig. 23) in Aleyrodinae, but no taxonomic decisions were taken regarding this fossil. Later, in the checklist of fossil Aleyrodidae, Szwedo & Drohojowska (2016: supplement p. 6), listed Heidea in Bernaeinae. This statement was not noted by Chen et al. (2020) listing again Heidea in Aleyrodinae referring to erroneous placement on the figure in Drohojowska & Szwedo (2011a).